2018
DOI: 10.18632/oncotarget.25320
|View full text |Cite
|
Sign up to set email alerts
|

Family history of breast cancer increases the risk of prostate cancer: results from the EPICAP study

Abstract: IntroductionFamilial aggregation is now well established with an increased risk of prostate cancer in patients with a family history of prostate cancer in first degree relatives. The aim of this paper was to investigate the role of family history of cancer in first degree relatives in prostate cancer risk.ResultsAs expected, a family history of prostate cancer in first-degree relatives was more frequent in cases than in controls (OR 3.10, 95% CI 2.32–4.15). A family history of early BCa (before age 50) in firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…A prospective study on 37,002 US men in the Health Professionals Follow-up Study showed that a family history of breast cancer in mothers only and sisters only was significantly associated with increased prostate cancer risk [19], and the results were consistent with those of two cohort studies [18, 26]. We also observed a positive association between history of breast cancer in daughters only and increased prostate cancer risk in cohort and case-control studies [23, 28]. However, other studies reported no significant association between prostate cancer risk and family history of breast cancer in mothers only, sisters only, and daughters only [24, 27].…”
Section: Discussionsupporting
confidence: 86%
“…A prospective study on 37,002 US men in the Health Professionals Follow-up Study showed that a family history of breast cancer in mothers only and sisters only was significantly associated with increased prostate cancer risk [19], and the results were consistent with those of two cohort studies [18, 26]. We also observed a positive association between history of breast cancer in daughters only and increased prostate cancer risk in cohort and case-control studies [23, 28]. However, other studies reported no significant association between prostate cancer risk and family history of breast cancer in mothers only, sisters only, and daughters only [24, 27].…”
Section: Discussionsupporting
confidence: 86%
“…Family associated PCa was first reported by Cannon et al in the Utah Mormon population almost forty years ago in 1982 [19]. Familial aggregation has since been well established and it is now widely accepted that men with a family history of PCa in firstdegree relatives are at increased risk of the disease [20,21]. In 2015, Liss et al reported men with a family history of PCa have a higher incidence of PCa (16.9% vs. 10.8%, p < 0.01) and higher PCa specific mortality (0.56% vs. 0.37%, p < 0.01) than men without a family history of PCa [22].…”
Section: Family History As a Risk Factor For Prostate Cancermentioning
confidence: 99%
“…However, men may also die from competing comorbidities associated with old age. Moreover, men with a family history, namely, men with first‐degree relatives with PCa, breast or ovarian cancer, have been associated with an increased risk of PCa 16 . Reports have also suggested that the early onset of PCa in a sibling may increase the risk of PCa diagnosis 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, men with a family history, namely, men with first‐degree relatives with PCa, breast or ovarian cancer, have been associated with an increased risk of PCa. 16 Reports have also suggested that the early onset of PCa in a sibling may increase the risk of PCa diagnosis. 17 Furthermore, Black men have been reported to have a 1 in 4 lifetime risk of being diagnosed with PCa and a 1 in 12 risk of dying from it, which is double the risk to White men, which were found to be 1 in 8 and 1 in 24, respectively.…”
Section: Introductionmentioning
confidence: 99%